Sustainable urban development in historic Cairo - Rashed, Haitham Farouk (2013)
Heritage is a constituent of the cultural tradition, and an important component of societal and community welfare. This comprehensive vision merges both tangible and intangible dimensions; architectural and historical values. As a result of globalisation, local communities of heritage sites have started to realise the significance of their influencing voices in shaping their lives and futures. Several rehabilitation and development initiatives have been selected for this study to review lessons learned from a variety of methodologies adopted for different historical districts of distinctive urban, political, and socio-economic contexts. Historic Cairo is home to the largest concentration of Islamic monuments in the world and was designated a world heritage site in 1979. Despite historic Cairo's international and national significance, it is highly vulnerable to negligence and deterioration as a consequence of modernisation and rapid changes in urban and cultural lifestyles. Historic Cairo has attracted numerous rehabilitation, preservation and restoration studies, proposals, and projects through governmental, national, and international efforts. These rehabilitation schemes however have lacked the sustainable urban development delivery in this heritage context. Moreover, most of the schemes neglected yet another significant dimension for sustainable urban development considered key to many successful schemes; community participation and involvement in the planning process. The study aims to fill the research gap identified to achieve sustainable urban development in historic Cairo. Thus, a thorough, evidence-based, and theoretically informed methodology has been proposed for developing a tailored intervention that attempts to tackle some of the most critical problems in historic Cairo. The present study adopts a mixed-method strategy with an in-depth case study to undertake a comprehensive analysis of the research problem. This mixed methodology has had the benefit of combining data collection techniques, interviews and questionnaire in order to explore more fully the context of the case study. The combination of methods has provided a basis for exploring how community participation plays a vital role in the success (or failure) of the delivery of a development intervention in historic Cairo. Results from questionnaires and interviews have provided a robust vision of how the bottom-up and top-down views complement each other to provide a foundation for the researcher to build the proposed intervention on. The analysed results are to provide recommendations to decision makers on how best to encourage and incorporate stakeholders' views in future interventions implemented within their rich historic context. Drawing from the survey results along with lessons learnt from other development initiatives in heritage sites, and complementing this with space syntax analysis techniques, a set of tailored design guidelines is generated for sustainable development in historic Cairo. The proposed design guidelines comprise recommendations that have dealt with the five main urban zones of historic Cairo based on the most critically required design principles for sustainable development; diversity and choice, distinctiveness/sense of place, users' needs, self sufficiency/participation, and pollution reduction. The proposed strategy has aimed to consider the development of the physical urban context of historic Cairo whilst enhancing the social, economic, and environmental aspects within the local community to guarantee the sustainable delivery and outcomes of the intervention.